FUNCTIONAL ADAPTATION OF THYROID GLAND IN POSTMENOPAUSAL WOMEN WITH AND WITHOUT DIABETES - Nadeem, Shehwar; Janjua, Qasim M.; Nasreen, Maimoona; Leghari, Qurrat-ul-ain; Iqbal, Amir; Cheema, Abdul Majeed; Malik, Samina (Pakistan Journal of Physiology, 2017)
Background: Prevalence of thyroid disorders in general population and in patients suffering from diabetes mellitus is inconsistent in different populations. The combined effect of thyroid dysfunction and diabetes in postmenopausal age may have its specific adaptations from the normal set up. The thyroid profile can provide a link between thyroid and diabetic postmenopausal women of variable ages. The study was designed to compare Thyroid stimulating hormone (TSH), Total thyroxine (TT4), Total triiodothyronine (TT3), Free thyroxine (FT4) and Free triiodothyronine (FT3) in non-diabetic postmenopausal, diabetic postmenopausal and premenopausal non-diabetic females. Methods: A total of 78 females from Lahore, Pakistan were recruited for the study and were divided into three groups: diabetic postmenopausal (n=32), non-diabetic postmenopausal (n=33) and premenopausal non-diabetic (n=13). Participant’s serum sample was collected after written informed consent and analyzed for the above mentioned thyroid parameters by using ELISA. Results: TT4 was significantly greater in diabetic post-menopausal as compared to premenopausal. In diabetic subjects TT3 and FT3 were significantly lower as compared to non-diabetic postmenopausal. Compared to diabetic postmenopausal subjects FT3 level was significantly greater in premenopausal subjects. Conclusion: Thyroid gland appears to adapt its function in postmenopausal diabetic and non-diabetics. However, studies on larger population are required for a clear picture. Pak J Physiol 2017;13(4):34–7